Temperature and solid properties effects on gas–liquid mass transfer - Ferreira, António (2010)
The knowledge about the effect of solid phase properties, at different temperatures, on gas–liquid transfer and the respective physical mechanisms has been poorly studied. In the present work, the temperature and solid properties (size and density) effects on the gas–liquid mass transfer characteristics in a bubble column were experimentally evaluated. Gas–liquid–solid systems formed by air/water/polyvinyl chloride (PVC) beads and air/water/expandable polystyrene (EPS) beads were used. For each system, volumetric liquid side mass transfer coefficient, kLa, was determined under different temperatures (20–35 ◦C), superficial gas velocities (up to 7.2 mm/s), solids sizes (210, 549 and 591 m) and concentration (up to 5 vol.%). The results show that the temperature plays an important role on mass transfer phenomena as kLa increases as temperature is increased. However, temperature does not have, significantly, influence on the solids effect on kLa. In what concerns the effect of the solids on kLa, a negative effect of their presence is observed being this effect more pronounced for the largest particles (for PVC). In addition, for the same solid size, a decrease in kLa occurs when the solid loading increases (observed in both cases, PVC and EPS). Complementary, bubble/particle interaction studies, using an image analysis technique, were also done aiming a better understanding of the effects of the two types of particles – PVC and EPS – on kLa values, being clearly confirmed that physical (e.g. density) and chemical properties of the solids are important parameters to be taken into account on mass transfer and hydrodynamic studies. Based on theoretical models for kL and a, an empirical correlation for kLa dependence on the experimental variables was developed. The experimental results were fitted with a mean deviation of 5%, that is similar to the experimental error (5%).